Outcome of Diagnostic Tests Using Samples from Patients with Culture-Proven Human Monocytic Ehrlichiosis: Implications for Surveillance - Childs, James E. (American Society for Microbiology, 1999)
We describe the concordance among results from various laboratory tests using samples derived from nine culture-proven cases of human monocytic ehrlichiosis (HME) caused by Ehrlichia chaffeensis. A class-specific indirect immunofluorescence assay for immunoglobulin M (IgM) and IgG, using E. chaffeensis antigen, identified 44 and 33% of the isolation-confirmed HME patients on the basis of samples obtained at initial clinical presentation, respectively; detection of morulae in blood smears was similarly insensitive (22% positive). PCR amplifications of ehrlichial DNA targeting the 16S rRNA gene, the variable-length PCR target gene, and the groESL operon were positive for whole blood specimens obtained from all patients at initial presentation. As most case definitions of HME require a serologic response with compatible illness for a categorization of even probable disease, PCR would have been required to confirm the diagnosis of HME in all nine of these patients without the submission of a convalescent-phase serum sample. These data suggest that many, if not most, cases of HME in patients who present early in the course of the disease may be missed and underscore the limitations of serologically based surveillance systems.